2008
DOI: 10.1002/chem.200801296
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Electron‐Rich cis‐Palladium(II) Complexes with Phosphine and Carbene Ligands as Catalytic Precursors in Suzuki Coupling Reactions

Abstract: A new imidazolinium ligand precursor [L(2)H]Cl (2) was prepared in 86 % yield. Compared with its imidazolium counterpart, [L(1)H]Cl (1), 2 is very sensitive to moisture and can undergo ring-opening reactions very readily. Palladium complexes with the ring-opened products from imidazolinium salts were isolated and characterized by X-ray crystallography. Theoretical studies confirmed that the imidazolinium salt has a higher propensity for the ring-opening reaction than the imidazolium counterpart. New mixed phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…This study, involving deproptonation of imidazolinium salts (1) with 2 revealed that the nature of products can be influenced by the presence of water either in the solvent or as hydrate and Nsubstituents on the ring [23,31]. Thus, N-benzyl substituted salt 1a in THF reacts only to give 5a as a result of hydrolysis of the expected NHC.…”
Section: Resultsmentioning
confidence: 99%
“…This study, involving deproptonation of imidazolinium salts (1) with 2 revealed that the nature of products can be influenced by the presence of water either in the solvent or as hydrate and Nsubstituents on the ring [23,31]. Thus, N-benzyl substituted salt 1a in THF reacts only to give 5a as a result of hydrolysis of the expected NHC.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling reaction between 2‐ tert ‐butylimidazo[1,2‐ a ]pyridine and diphenylacetylene was used as the benchmark reaction and our previous conditions of using 2.5 mol‐% of the palladium complex as precatalyst, a reaction temperature of 90 °C, Cu(OAc) 2 as base, a reaction time of 16 h, dimethylformamide (DMF) as solvent, and n ‐tetrabutylammonium bromide (TBAB) as phase‐transfer catalyst were employed Entry 1 clearly shows that the ionic NHC complex 1a was the most effective, which afforded the coupled product in a good yield of 74 %. The neutral dichloropalladium(II) complex 1b bearing the same NHC ligand and tricyclohexylphosphine, reported by us earlier, was much less effective (entry 2). The palladium(II)–NHC complex with an IMes ligand [IMes = 1,3‐bis(2,4,6‐trimethylphenyl)imidazol‐2‐ylidene] has been proven to be highly effective in various cross‐coupling reactions .…”
Section: Resultsmentioning
confidence: 63%
“…Side products derived from the reduction or homocoupling of the aryl halides were not detected at all or were observed only in trace amounts. The higher activities of the PCy 3 complexes (Entries 3 and 4) relative to the PPh 3 complexes (Entries 1 and 2) can be attributed to the faster de‐coordination of the labile PCy 3 ligand and facile formation of the Pd 0 species 9. However, the close activities of complex 1 and 2 should result from the presence of the PyS group.…”
Section: Resultsmentioning
confidence: 97%